Effect of nozzle type on local scour in water jets: An experimental study - Kartal, Veysi; Emiroglu, M. Emin (Pergamon-Elsevier Science Ltd, 2023)
Water jets are generally used in civil, environmental, and chemical engineering and other disciplines. Venturi nozzles are crucial devices that are applied in jet aeration systems. The prediction of scour hole geometry in non -cohesive sands is a challenge for hydraulic engineering. Thus, this study presents the results of a laboratory investigation on the geometric properties of the scour produced by jets with different nozzle types in non -cohesive sands. Several experimental runs were conducted to investigate the scour geometry caused by in-clined water jets from Venturi and circular nozzles for unsubmerged conditions. The results were analyzed to discover the influence of the densimetric Froude number, relative tailwater depth, impact angle, and dimen-sionless impingement length on the scour hole geometry based on the jets from circular and Venturi nozzles. Consequently, the maximum scour depths obtained for the Venturi nozzle were approximately 1.4 times deeper for the small diameters of the circular nozzle and 2.4 times deeper for large diameters. In conclusion, the findings can be useful in hydraulic applications such as agricultural irrigation, liquid-fertilizer injection, aeration, oxygen transfer, and wastewater-potable water treatment and aquaculture, outlets of culverts, pond water aeration systems, and storm drainage pipes.
Keywords: Local scour; Nozzle; Plunge pool; Venturi; Water jet